How consumer culture controls our kids : cashing in on conformity - Hill, Jennifer Ann (Santa Barbara, California : Praeger, an imprint of ABC-CLIO, LLC, 2016)
"In this critique of America's consumption-based society, author Jennifer Hill chronicles the impact of consumer culture on children--from the evolution of childhood play to a child's self-perception as a consumer to the consequences of this generation's repeated media exposure to violence. Hill proposes that corporations, eager to tap into a multibillion-dollar market, use the power of advertising and the media to mold children's thoughts and behaviors. The book features vignettes with teenagers explaining, in their own words, how advertising determines their needs, wants, and self-esteem. An in-depth analysis of this research reveals the influence of media on a young person's desire to conform, shows how broadcasted depictions of beauty distort the identities of children and teens, and uncovers corporate agendas for manipulating behavior in the younger generation. The work concludes with the position that corporations are shaping children to be efficient consumers but, in return, are harming their developing young minds and physical well-being." -- Publisher's description
Culture jamming and other ventures -- The children's culture industry -- I buy, therefore I am -- For and against the child as a consumer -- Conformity, creativity, and the mechanisms of persuasion -- Democracy versus consumer capitalism -- Deconstructing consumerism: from the voices of young people -- Primed to consume -- Appendix: interview questionnaire.
Includes bibliographical references and index.
Keywords: Child consumers -- United States; Consumption (Economics) -- Social aspects -- United States; Child development -- United States